Characterization of a new vacuolar membrane aquaporin sensitive to mercury at a unique site. - Daniels, M J (1996)
The membranes of plant and animal cells contain aquaporins, proteins that facilitate the transport of water. In plants, aquaporins are found in the vacuolar membrane (tonoplast) and the plasma membrane. Many aquaporins are mercury sensitive, and in AQP1, a mercury-sensitive cysteine residue (Cys-189) is present adjacent to a conserved Asn-Pro-Ala motif. Here, we report the molecular analysis of a new Arabidopsis aquaporin, delta-TIP (for tonoplast intrinsic protein), and show that it is located in the tonoplast. The water channel activity of delta-TIP is sensitive to mercury. However, the mercury-sensitive cysteine residue found in mammalian aquaporins is not present in delta-TIP, or in gamma-TIP, a previously characterized mercury-sensitive tonoplast aquaporin. Site-directed mutagenesis was used to identify the mercury-sensitive site in these two aquaporins as Cys-116 and Cys-118 for delta-TIP and gamma-TIP, respectively. These mutations are at a conserved position in a presumed membrane-spanning domain not previously known to have a role in aquaporin mercury sensitivity. Comparing the tissue expression patterns of delta-TIP with gamma-TIP and alpha-TIP showed that the TIPs are differentially expressed.